Pro Windows Server AppFabric - Kaufman, Stephen (Apress, 2012)
This book begins by covering an overview of AppFabric. Next, it covers decision points for when to select AppFabric or BizTalk. As you move through the chapters, you will learn about developing an AppFabric application in the context of a practical business scenario, as well as by looking at the architecture of AppFabric and the services that it provides. The latter part of the book walks you through advanced concepts, as well as how to deploy, track, and monitor applications.